Mequindox-Induced Kidney Toxicity Is Associated With Oxidative Stress and Apoptosis in the Mouse - Liu, Qianying; Lei, Zhixin; Guo, Jingchao; Liu, Aimei; Lu, Qirong; Fatima, Zainab; Khaliq, Haseeb; Shabbir, Muhammad A. B.; Maan, Muhammad Kashif; Wu, Qinghua; Dai, Menghong; Wang, Xu; et al. (Frontiers in Pharmacology, 2018)
Mequindox (MEQ) is a synthetic antimicrobial agent of quinoxaline-di-N-oxides (QdNOs) widely used in China. Previous studies have identified the kidney as one of the main target organs for toxicity of the QdNOs. However, the mechanism underling the kidney toxicity caused by QdNOs in vivo still remains unclear. The present study aims to explore the molecular mechanism of kidney toxicity in mice after chronic exposure to MEQ. MEQ resulted in the oxidative stress, apoptosis and mitochondrial damage in kidney of mice. Meanwhile, MEQ up-regulated Bax/Bcl-2 ratio, disrupted mitochondrial permeability transition pores, and subsequently, caused cytochrome c release and a cascade activation of caspase, eventually induced apoptosis. The oxidative stress mediated by MEQ might lead to mitochondrial damage and apoptosis in a mitochondrial dependent apoptotic pathway. Furthermore, up-regulation of the Nrf2-Keap1 signalling pathway was also observed. Our findings revealed that changes in oxidative stress, mitochondrial dysfunction, and upregulation of the Nrf2-Keap1 gene family were associated with the kidney apoptosis mediated by MEQ in vivo.